Desain Road Barrier For Road Junction (Case Study: Flyover Jalan Jakarta, Bandung) - Amar Mufhidin; Asep Maksum (Jurnal Pendidikan Teknik Bangunan, 2021)
A road barrier is a building structure that complements the road and serves as a traffic parking or traffic control device on the highway, as well as a barrier or barrier on parking lots and public roadways. Concrete road barriers are precast concrete products made from concrete composite parts, which are made up of a sequence of iron rods cast in concrete. The goal of this road barrier design is to determine how many dimensions of road barrier thickness and reinforcement are required, particularly for the case study of the Jakarta roads in Bandung. The dimensions of the road barrier may be observed from the results of calculations and loads on the flyover construction of the Jakarta road: height 110cm, top width 20cm, bottom width 50cm, main reinforcement D13-200, and divider reinforcement D13-100.